Quality of two brands of cooking oil for frying peanuts - Cortez, Patrocinia R.
This study compared the changes in free fatty acid values and smoke points of Baguio oil and Fresco oil when heated alone and when used for frying peanuts continuously at 177°C for two hours. Results from heating the two oils alone showed increase in free fatty acid value and decrease in smoke point with no significant differences within the same brand with hours of heating. Frying peanuts significantly increased the acid value of both oils and lowered their smoke points as well. No significant differences were detected between brands in terms of acid value but statistical analysis showed that Baguio oil had a significantly lower smoke point than Fresco oil after every hour of frying. The peanuts fried in each brand of oil were similar in flavor. Peanuts fried during the second hour in Baguio oil carried the burnt oil flavor; those fried on the first hour in this oil had the characteristic flavor of peanuts and off-flavors were absent. Peanuts fried in Fresco oil during the first and second hours were free from off-flavors.